Mineralogical characterization of bulk concentrate to reduce arsenic and antimony by alkaline leaching, in Peru - Ramos Peralta, Julio (2023)
The presence of contaminants such as arsenic and antimony in polymetallic concentrates can lead to economic losses due to penalties imposed in commercialization contracts when the permissible limits are exceeded. For this reason, the present study focuses on supporting the reduction of these contaminants through the application of alkaline leaching using NaOH and Na2S in polymetallic concentrates. Optical microscopy tests indicated the presence of species with a high content of arsenic and antimony known as gray coppers and silver sulfosalts. Based on the mineralogical characterization, it was possible to solubilize 93.79% of arsenic and 96.21% of antimony, in a time of four hours, at a temperature of 100°C, with a dosage of 48 kg/TM of sodium hydroxide and 13 kg/TM of sodium sulfide, at a granulometry of 10% - 37μ. It was achieved to reduce the arsenic grade to 0.45% and the antimony grade to 0.24% and increase the copper grade to 23.60% in the bulk concentrate, increasing profitability for the sale of contaminant-free concentrates.